تقدير التلوث بالعناصر الثقيلة في نباتات المنطقة المحيطة بمحطة كهرباء الزبيدية الحرارية في محافظة واسط - eabd, haytham; كاظم شبوط أستبرق (Journal of College of Education, 2022)
Abstract The study aims to know the effect of the Al-Zubaidiyah Thermal Power Station in Wasit Governorate on pollution and the plants surrounding the station, as the results of the analysis of plant characteristics showed that most of the polluting elements came within the permissible limits (copper, zinc, manganese, iron), either of the following elements (nickel, Lead, cadmium), it came within the limits permitted locally and internationally, and it became clear that the cobalt element exceeded the permissible limits in the following locations (S1 - S2 - S3 - S6 - S7 - S8 - S9 - S10 - S11 - S12 - S16 - S17 - S18) -S20), either the other sites came within the permissible limits locally and internationally.